AI-Driven E-Recruitment in Education and Science: Moving Towards Good Governance, Prevention of Corruption, Administrative Transparency, and Bias-Free Decision-Making - Massimo Pollifroni; Adrian Ioana; Ionela Luminita Canuta (Bucuroiu); Francesco Pollifroni (Business Ethics and Leadership, 2025)

(untitled)
The paper covers the issue concerning the current recruitment systems in higher education, a European-level starting point of the reform launched by the Bologna Process in 1999. The Bologna Process was born in 1999 as an intergovernmental collaboration agreement in the higher education system. Its objective was to build a European higher education area based on principles and criteria shared between the participating countries. Twenty-five years after the agreement came into force, it is possible to take stock of the effects that European rules have had on the processes of hiring teaching staff (researchers, associate professors and full professors). While on the one hand the reform has introduced a standardization of processes (strength), on the other hand some critical issues (weaknesses) have been identified. The current recruitment systems in higher education are unsatisfactory, due to repeated gaps in the ethical profiles of the procedures, which have produced two collateral effects: 1) an increase in administrative appeals and 2) an increase in the average age of successful candidates. The paper proposes an innovative and theoretical e-recruitment model named NCHE-4-R-AP-FP to overcome these critical issues. The model identifies the need to transform the present procedures from non-comparative procedures to comparative procedures, should change its name and become the reference procedure for all three academic levels. Therefore, it would be possible to foresee the creation of 1) a comparative procedure for researchers, which should evaluate only research activity; 2) a comparative procedure for full and associate professors, which should evaluate research, teaching, institutional and third mission activities (with the exclusion for the latter of those already included in research activity, such as patents). The fundamental differences between the model and existing ones are: 1) AI integrated into current e-government processes, 2) abolition of physical evaluation committees and 3) transformation of recruitment processes into e-recruitment processes. The advantages of the proposed model consist in overcoming the previously exposed critical issues, although the most archaic academic system itself will probably advance the greatest resistance to the proposal.